Pathogenicity of betanodavirus strains in Asian seabass (Lates Calcarifer) under temperature fluctuation stress - Khairul Asri, Muhammad Safwan; Abdullah, Azila; Nawi, Mohd Firdaus; Mohd Idris, Shaharah; Ramly, Rimatulhana; Mansor, Nur Nazifah (Fisheries Research Institute (FRI), Department of Fisheries Malaysia, 2024)
Viral nervous necrosis (VNN) caused by betanodavirus is responsible for mass mortality in various marine cultured fish species. VNN can be transmitted horizontally and vertically. In this study, three betanodavirus strains (BE2006, AVA, and KL0022) were obtained from National Fish Health Research Centre (NaFisH) and cultured in the E-11 cell line. The median tissue culture infective dose (TCID50) for all isolates was determined before being used in in vivo experiments. The TCID50 of KL0022, BE2006, and AVA were 104 TCID50/mL, 107 TCID50/mL, and 106 TCID50/ mL, respectively. The KL0022 strain had the lowest TCID50, followed by that of AVA and BE2006. Subsequently, 360 healthy juvenile Asian seabass (5 ± 2 g) were divided equally into eight tanks to represent four treatment groups with duplicates: Group 1 (AVA), Group 2 (BE2006), Group 3 (KL0022), and Group 4 (negative control). The fish were observed daily for clinical signs or mortality. On the appearance of clinical signs or mortality, the fish were killed immediately and underwent a reverse transcriptase–PCR (RT-PCR) and virus cell culture. The experiment was terminated after 30 days. The clinical signs observed among the sick and dead fish were darker body colouration and lethargy. The highest mortality was recorded in the KL0022 group, indicating that the strain had the highest virulence, followed by the AVA and BE2006 groups. All dead and sick fish from the treatment groups were positive for betanodavirus by RT-PCR, while the dead fish from the negative control group tested negative.